Studying Russian Religion Since the Collapse of Communism - Coleman, Heather (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
This review article surveys the field of the religious history of Russia since the fall of the Soviet Union. Increased accessibility to the archives in the early 1990s coincided with historiographical developments such as the “new cultural history” and the “lived religion” approach to the study of religious cultures, favouring a renewed interest in religious topics. The article argues that the lived religion approach has allowed scholars to rethink the classic question of the relationship between church and state, to demonstrate the significance of religion to the social, intellectual, and political transformations experienced in late imperial and early Soviet Russia, and to reconceptualize Russian Orthodoxy’s relationship with modernization and modernity. This research demonstrates the need to correct the traditional neglect of the Orthodox experience in histories of religion in Europe and in theorizing religious change and secularization in the modern era.